EFFECT OF DIETARY PROBIOTICS SUPPLEMENTATION ON GROWTH PERFORMANCE OF ROHU, LABEO ROHITA FINGERLINGS - SAYANTI SAHA,; MOHAMMAD ABUL HASSAN,; ANIL PRAKASH SHARMA, (International Journal of Pharma and Bio Sciences, 2015)
The effect of dietary supplementation of commercial probiotics Bifilac® on growth of rohu, Labeo rohita fingerlings were evaluated. Experimental diet (ED) was supplemented with Bifilac® (3g/kg diet). Reference diet (RD) was not supplemented with Bifilac®. The feeding trial was conducted using L. rohita fingerlings (5.30±0.01 g) for 60 days in triplicates. The groups D1 and D2 were fed daily with RD and ED, respectively, while the D3 group was fed alternately with RD and ED at an interval of 7 days. All experimental groups were fed ad libitum twice daily at 8:00 am and 2:00 pm. The growth performance and feed utilization efficiencies were highest for D2. Carcass protein content was found highest for D2. The digestive enzyme activity and the heterotrophic bacterial count of gut were highest for D2 fish group. So, daily dietary supplementation of Bifilac® resulted in improved growth and feed utilization efficiencies of L. rohita fingerlings.